How to Manage Public Investment during a Postcrisis Recovery - Allen, Richard (IMF How To Notes; How-To Note, 2021)
Public investment is likely to be an important component of any postcrisis recovery program. As countries work to ensure a smart, green, fair recovery, investing in modern, resilient, and efficient infrastructure assets will be key. This How to Note discusses how countries should manage public investments to recover from the COVID-19 pandemic and similar crises. It provides countries with guidance on making efficient use of public investment to support economic recovery on three different capacity levels: basic, medium, and advanced.